Talking text: Exploring SMS and e-mail use by Australian talkback radio listeners. (1st April 2016) - Ewart, Jacqui; Ames, Kate
Research into talkback radio has provided a great deal of information about shock jocks and their interactions with audiences, their political power and the power of radio to mobilize its audiences in negative ways. Talkback radio has been traditionally perceived as a participatory form of media, albeit limited by various gatekeeping and rules of access. However, the nature of talkback with its traditional reliance on voice and performance is changing as programmes are increasingly offering audience members the opportunity to contribute to programmes via e-mail, Short Messaging Service (SMS) and, more recently, websites and social media. This article contributes to an under-explored area of talkback radio studies by examining audience 'participation' in talkback programmes via SMS and e-mail. It draws data from focus groups with audiences of twelve Australian commercial and non-commercial talkback radio programmes to discover why some study participants use SMS and e-mail and why some do not contribute via these technologies. The article also examines, in what circumstances and for what purposes these talkback radio listeners use these technologies. Inductive coding was used to analyse the data through the computer program NVivo. We conclude that while study participants strongly associated talkback with phone calls, e-mail and SMS are largely accepted as regular methods of contributing to and communicating with talkback radio programmes. There is much more work to be undertaken on the topic of non-verbal contributions to talkback radio, particularly with the increasing use of social media sites such as Facebook and Twitter, which this article has not explored.